Functional organization of the hepatitis B virus enhancer. - Dikstein, R (1990)
We have studied the functional constituents of the hepatitis B virus enhancer in a number of cell lines. The sequence of this enhancer, being embedded within an open reading frame of the virus, is in part evolutionarily frozen and therefore serves as a good model to investigate the fundamental enhancer elements. The hepatitis B virus enhancer contains three functionally important DNA sequence elements, EP, E, and NF-1a, each of which is bound by a distinct protein(s). The synergistic action of these elements accounts for all of the enhancer activity in a nonliver cell line and for most, but not all, of the activity in liver-derived cell lines. Multimers of the E but not of the EP element act as an autonomous enhancer. Conversely, a single element of either the E or the NF-1a element can act only when linked to the EP element. These results suggest that EP is a crucial enhancer element that acts only in interaction with a second enhancer element with intrinsic enhancer activity. Interestingly, a highly similar enhancer structure is found in a number of distinct viruses.